Development of photoremovable protecting groups - Literák, Jaromír (2006)
The objective of this thesis is to contribute to the development and applications of the photolabile protecting groups (PPGs). The first chapter contains a short review dealing with the most important photoremovable protecting groups and photolinkers. It is aimed to provide the reader the newest facts concerning the reaction mechanisms and PPG applications. The following chapter summarizes our results. We exploited the photochemical behavior of 2-alkylphenyl ketones, which has been thoroughly studied in our research group since 2000 when Petr Klán proposed 2,5-dimethylphenacyl (DMP) chromophore as a photoremovable protecting group for carboxylic acids. We successfully applied the DMP chromophore to mask alcohols and phenols, the development of new photolabile linker, which contains 2-methylphenacyl moiety, is described. Short section is devoted to the photoenolisation of cyclic ketones, 4,7-dimethylindan-1-one and 4,7-dimethylindan-1,3-dione.